SAT0199 POLYAUTOIMMUNITY IN SYSTEMIC LUPUS ERYTHEMATOSUS. DATA FROM A LARGE SPANISH COHORT: SPANISH SOCIETY OF RHEUMATOLOGY REGISTRY OF PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS (RELESSER). (June 2019) - Mena-Vázquez, Natalia; Fernandez-Nebro, Antonio; Rúa-Figueroa, Iñigo; Galindo-Izquierdo, María; Ovalles, Juan; Olivé, Alejandro; Calvo, Jaime; Menor-Almagro, Raúl; Muriel, Eva Tomero; Isacelaya, Esther Uriarte; Boteanu, Alina; Andres, Mariano; et al.
Abstract : Background: Objectives: Estimate the frequency of the association of SLE with other autoimmune diseases in a large Spanish cohort of patients with systemic lupus erythematosus (SLE). Methods: Design: RELESSER is a nationwide multicentre, hospital-based registry of SLE patients. This is a cross-sectional study. Patients : Unselected consecutive adult patients with SLE, classified according to the ACR 1997 criteria. Main outcome: Polyautoimmunity was defined as patients who fulfilled criteria for SLE and other autoimmune disease: autoimmune thyroiditis, rheumatoid arthritis, systemic sclerosis or inflammatory myopathy and mixed connective tissue disease. Multiple autoimmune syndrome (MAS) was defined as patients who meet SLE criteria and at least two other autoimmune diseases. Statistical analysis: Descriptive. Multiple logistic regression analysis to investigate the possible risk factors for polyautoimmunity in patients with SLE. Results: From 3679 (91.4%) patients included in the registry, 501 (13.6%) had Polyautoimmunity. The characteristics are showed in Table. The most frequent polyautoimmunity types associated with SLE were: autoimmune thyroiditis (7.5%), other connective tissue disorders (7.1%). Other autoimmune diseases not considered within the scope of Polyautoimmunity was 12.8% for Sjögren's syndrome and 12.7% for antiphospholipid syndrome. A family history of SLE was 12.4% and MAS in 10.2%. The multivariate analysis identified age (odds ratio [95% CI], 1.01 [1.00-1.02]), sex (3.00 [1.48-6.04]), Raynaud's phenomenon (1.79 [1.34-2.39]), pulmonary fibrosis (2.88 [1.32-6.30]), Ro-La autoantibodies (1.68 [1.20-2.36]), antiRNP (1.79 [1.32-2.42]) and treatment with methotrexate (1.54 [1.08-2.18]) or with antimalarials (0.57 [0.41-0.78]) as factors associated with polyautoimmunity. Conclusion: SLE patients associated poliautoimmunity in 14%, MAS in 2%. More studies are needed to better understand the increase of polyautoimmunity in these patients. Disclosure of Interests: Natalia Mena-Vázquez: None declared, Antonio Fernandez-Nebro: None declared, Iñigo Rúa-Figueroa: None declared, María Galindo-Izquierdo: None declared, Juan Ovalles: None declared, Alejandro Olivé Grant/research support from: ND, Consultant for: ND, Paid instructor for: ND, Speakers bureau: ND, Jaime Calvo Consultant for: Bristol-Myers Squibb, Janssen, Celgene, Sanofi Genzyme, Speakers bureau: Bristol-Myers Squibb, Raúl Menor-Almagro: None declared, Eva Tomero Muriel: None declared, Esther Uriarte Isacelaya: None declared, Alina Boteanu: None declared, Mariano Andres: None declared, Mercedes Freire González: None declared, J. Narváez Consultant for: Bristol-Myers Squibb, Tomas Vazquez Rodriguez: None declared, Ricardo Blanco: None declared, José A Hernandez Beriain: None declared, Jesus Ibañez: None declared, Enrique Raya: None declared, Joan Calvet: None declared, Jose M Pego-Reigosa: None declared